Vegetaion of the southern range of Junggar Alatau mountains (Eurasian Journal of Ecology, 2018)
The Junggar Alatau mountain system stretches in the latitudinal direction at 450 km between N 44 and 46°. It consists of mainly two parallel,high mountain ranges: the northern and southern. Vegetation occupies anintermediate position between the Northern Tien Shan and the Altai mountains. Vegetation of the southern range has features of typical Central Asianmountain systems (Cerasus tianschanica, Bothriochloa ischaemum, Krascheninnikovia ceratoides, Kochia prostrata) as well as some typical Siberianspecies (Abies sibirica, Trollius altaicus, Atragene sibirica). The regularitiesof altitudinal zonality of vegetation in the southern range of Junggar Alataumountains are studied. The following belts are identified: piedmont deserts;mountain steppe with sub-belts of desert and meadow steppes; forest-meadow belt; subalpine meadows, steppes and elfin woods; cryophytic (alpine)meadows and steppes. Forest-meadow belt is presented by fragments on theslopes of northern exposure. Small-lived and coniferous-deciduous forestsgrow only in the river valleys. Sub-belt of typical steppe is not found dueto aridity of the southern range and plowing foothill plains. Characteristicsof main types of vegetation are done for each altitudinal belt. According toecological-physiognomic classification, in the Junggar Alatau range there are5 vegetation types: arboreal, shrubby, dwarf semi shrub, meadow, steppe.Key words: ecology, vegetation, flora, species, Jungar Alatau, altitudinal zoning, kriofit.